MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) MELALUI STRATEGI PEMBELAJARAN QUANTUM TEACHING DENGAN PENGGUNAAN MEDIA LINGKUNGAN - Nurhaty Purnama Sari; Destaria Sudirman (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
This research was a Classroom Action Research (CAR) which carried out consisting of two cycles and each cycle consisting of 1 face-to-face activity, with each face-to-face for 2 hours of lessons (2x40 minutes). Each cycle consists of 4 stages, namely planning, implementing, observing, and reflecting. This study aims to: 1) Describe about implementation of science learning material classification of living things in IPA subjects for students of Package B Tanjung Gundap by implementing Quantum Teaching strategies using environmental media; 2) To determined the increase in science learning achievement matter classification of living things in science subjects for students of Package B Tanjung Gundap  by applying Quantum Teaching learning strategies with environmental media. Organizing students in groups to complete assignments where in cycle I the interaction and discussion between group members was not good. But with the teacher's guidance taking turns in each group, in the second cycle the interaction and discussion could run more optimally. Student learning outcomes with quantum teaching learning strategies with environmental media obtained 70.96% in cycle I and 90.32% in cycle II.